In the margins of composition - Denyer, Frank (Vision edition, 2019)
Frank Denyers creative impetus has taken him all over the world, from the UK to Japan, Senegal to the US on a lifetime quest to cultivate an intangible musical territory. In the Margins of Composition brings together reflections on the obsessions of a life spent in contemplation and creation, its impulses and influences with a personal review of his works and constitutes an indispensable and concise personal window on a unique artistic journey.